Differences between Spinocerebellar Ataxias and Multiple System Atrophy-Cerebellar Type on Proton Magnetic Resonance Spectroscopy - Lirng, Jiing-Feng (Public Library of Science, 2012)
PURPOSE: A broad spectrum of diseases can manifest cerebellar ataxia. In this study, we investigated whether proton magnetic resonance spectroscopy (MRS) may help differentiate spinocerebellar ataxias (SCA) from multiple systemic atrophy- cerebellar type (MSA-C). MATERIAL AND METHODS: This prospective study recruited 156 patients with ataxia, including spinocerebellar ataxia (SCA) types 1, 2, 3, 6 and 17 (N = 94) and MSA-C (N = 62), and 44 healthy controls. Single voxel proton MRS in the cerebellar hemispheres and vermis were measured. The differences were evaluated using nonparametric statistic tests. RESULTS: When compared with healthy controls, the cerebellar and vermis NAA/Cr and NAA/Cho were lower in all patients(p<0.002). The Cho/Cr was lower in SCA2 and MSA-C (p<0.0005). The NAA/Cr and Cho/Cr were lower in MSA-C or SCA2 comparing with SCA3 or SCA6. The MRS features of SCA1 were in between (p<0.018). The cerebellar NAA/Cho was lower in SCA2 than SCA1, SCA3 or SCA6 (p<0.04). The cerebellar NAA/Cho in MSA-C was lower than SCA3 (p<0.0005). In the early stages of diseases (SARA score<10), significant lower NAA/Cr and NAA/Cho in SCA2, SCA3, SCA6 or MSA-C were observed comparing with healthy controls (p<0.017). The Cho/Cr was lower in MSA-C or SCA2 (p<0.0005). Patients with MSA-C and SCA2 had lower NAA/Cr and Cho/Cr than SCA3 or SCA6 (p<0.016). CONCLUSION: By using MRS, significantly lower NAA/Cr, Cho/Cr and NAA/Cho in the cerebellar hemispheres and vermis were found in patients with ataxia (SCAs and MSA-C). Rapid neuronal degeneration and impairment of membrane activities were observed more often in patients with MSA-C than those with SCA, even in early stages. MRS could also help distinguish between SCA2 and other subtypes of SCAs. MRS ratios may be of use as biomarkers in early stages of disease and should be further assessed in a longitudinal study.